2011
DOI: 10.1155/2011/293926
|View full text |Cite
|
Sign up to set email alerts
|

Statistical Survey of Deaths from Nonmelanoma Skin Cancer in Japan during 54 Years

Abstract: The author analyzed the annual trends in the number of deaths from nonmelanoma skin cancer (NMSC) from 1955 to 2008 in Japan on the basis of the data from the Vital Statistics of Japan. The general trends in the number of deaths from NMSC were downward between 1979 to 1994, but upward after 1995. The general trends in age-standardized death rates were roughly downward, although the death rates plateaued after 1995. The recent annual increased ratio of deaths from NMSC was 3.8% (95% confidence interval: 2.7 ∼ 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
4
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 21 publications
3
4
0
Order By: Relevance
“…Recurrence rate is also higher in immunosuppressed patients. In the present study, recurrence was documented in 13% of patients, in line with the 7%‐13% rate reported in previous studies . The median time to recurrence was 2 years.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Recurrence rate is also higher in immunosuppressed patients. In the present study, recurrence was documented in 13% of patients, in line with the 7%‐13% rate reported in previous studies . The median time to recurrence was 2 years.…”
Section: Discussionsupporting
confidence: 92%
“…In the present study, recurrence was documented in 13% of patients, in line with the 7%-13% rate reported in previous studies. 26,[40][41][42][43][44][45][46][47][48][49] The median time to recurrence was 2 years. Similarly, Martinez et al 45 reported a metastatic recurrence rate of 5%-8%, usually during the second year after surgical treatment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…NMSCs have been shown to be BCCs in 80% of instances, and 20% are SCCs [17]. Our BCC and SCC rates were observed to be close to these percentages.…”
Section: Discussionsupporting
confidence: 80%